Physicochemical Properties of Balanites aegyptiaca (Laloub) Seed Oil - Fregon, Mohamed Elmustafa; Shakak, Mahdi Abbas Saad (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The main goal of this research was to study the physical and chemical properties of Balanites. aegyptiaca (laloub) oil.Two kilograms of Balanites aegyptiaca fruit were purchased from local market in Khartoum, Sudan. Fruits were then crushed using a steel hammer and seeds were then obtained. One kilogram of seeds was collected and was then ground using grinding machine. Processed ground seeds were then eventually ready for further analysis.The results revealed that B. aegyptiaca seed contain considerable percentage of moisture (3.10%) , oil (42.95%) ,protein (31.08%), fiber (12.64%), ash (3.19%) and carbohydrate (7.04%) on dry matter basis .Also the seeds contained different minerals e.g calcium (0.41mg), sodium (0.09mg), magnesium (0.13mg) phosphorus (0.30mg) and potassium (1.09mg) per 100g dry matter (DM).Also, the results of the physicochemical evaluation of B. aegyptiaca oil showed that it contains viscosity 19.63 cp, density 0.9109 , refractive index 1.483, colour 7.633 (R.y.b), free fatty acid 3.06%, peroxide value 1.18 (meq O2 /kg) , saponification value 224.63 (mg KOH/g), iodine value 122.42 and acid value 1.53 (mg KOH/g). The fatty acid profile of B. aegyptiaca seed oil showed that it contains linoleic acid 34.36%, palmitic acid 13.37%, stearic acid 15.03% and oleic acid 28.57%. From the previous physicochemical tests of B,aegyptiaca oil could be used for edible purpose.